Dinamika Psikologis Berhadapan dengan Kematian pada Petugas Palang Hitam - Andreas Corsini Widya Nugraha; Hanna Rahmi; Yunika Balsa (Fakultas Psikologi Universitas Pancasila, 2017)
The purpose of this study is to understand how the psychological dynamics of Palang Hitam officers. The Jakarta Parks and Cemetery Department has a special team ready to evacuate the corpse. They are known as the Palang Hitam Team. Their duty is to take care of abandoned and neglected corpse. Every experience that had experienced by a Palang Hitam officers forms a pattern and its won psychological dynamics. Psychological dynamics of Palang Hitam officers become interesting because they are idiocentric, as different from the experience of people in general. The work adjacent to the unnatural death and the frequent handling intensity creates the psychological dynamics of the concept of death itself to Palang Hitam officers. Methods of data collection were done by interview method, observation, group discussion, and documentation, conducted on four participants. The study found five findings on the psychological dynamics of Palang Hitam officers, based on experiences of daily interaction with death. The experiences of interacting with the object of death form a pattern of psychological dynamics in Palang Hitam officers, such as anxiety when confronted with close relatives who experience death, self-acceptance, and coping mechanisms are the findings of this study.